BENTUK PENYAJIAN TARI PUTRI BERHIAS DI KOTA LUBUKLINGGAU - Fadhilah Amalia Hasanah; Herlinda Mansyur; Afifah Asriati (SENDRATASIK UNP, 2018)
AbstractThis article aims to describe the performance of Putri Berhias dance in Lubuk linggau city, since Putri Berhias dance is a traditional dance which has not been researched as well as its documentation data. With the presence of  documentation of Putri Berhias dance into a form of writing, it is expected that the dance still preserved as cultural identity and the identity of Lubuk linggau city. Data obtained from the results of documents study, observation, interview and documentation. In this study, the researcher used triangulation to valid the data, that was a kind of technique which utilized something else.The research showed that the performance of Putri Berhias dance in Lubuklinggau city was in the form of purely representational. Its form  included elements or main element and supporting dance. Those elements were the motions of Putri Berhiasdance  which consists of thirteen kinds of motion maknawi. The design of the floor with  pattern of horizontal, vertical and diagonal lines. Music design composed of traditional instruments, accordion, Melayu drums, rebana, and tambourine. Make up used is beautiful. Costumes worn were baju kurung, songket limas, and kebo munggah necklace, kembang murai , kano bracelet, lotus, earrings, gandik pilis, pending, and cempako. Putri Berhias dance used selendang as property. It could be performed on the proscenium stage and open areas.Key words: Dance performance, Putri Berhias